APLIKASI ALAT BANTU PEMBELAJARAN VISUALISASI FINITE STATE AUTOMATA (Versi : Pembuktian Graph ke Tupel) - Masayu Jamilah; Wawan Nurmansyah (IIB Darmajaya, 2018)
Learning media that has been widely created and implemented in high schools and universities will certainly help students understand existing subjects, especially subjects related to theoretical arithmetic. Mathematical logic is certainly widely used in the development of computerization, computerization in the development of computer applications also has to do with arithmetic relations for the part of the process.Software engineering methods use prototypes to develop or develop system applications that have several steps, such as: Listen to Customer, Build / Revise mock-ups, Costumer Test. Completion of the stages of building automata learning applications is part of the development stage of the automata learning system application with the application of Finite State Automata (FSA).Application results with a GUI-based (User Interface Graph) design implemented to support the automata course material. Graphic automata application implementation to show the relationship between states resulting from the logic of the relationship results from each existing node. The resulting application has 2 important parts for the design stages, namely: process design (flowchart) and interface (Morkup). The results of all designs are further implemented with the Borlan Delphi visual programming language application. Testing with black box is done with a visual Graph verification scenario which is inputted with the suitability of the input and which is not to see the results of Tupel based on the graph that is successful and not successful. Keywords: automata, learning, application, Graph, Tupel.